Moving from tools to deliverables and outcomes. Proceedings of the annual meeting of cluster CC2.1 (Improving RTB planting material and access to new varieties) - Kilwinger, Fleur B.M.; Pircher, T.; Almekinders, Conny J.M.; Andrade-Piedra, J.L.; McEwan, M. (International Potato Center, 2018)
Twenty-eight members (11 women, 17 men) of the CGIAR Research Program on Roots, Tubers and Bananas (RTB) crosscutting cluster (CC) 2.1 Quality seeds and access to improved varieties, attended the workshop “Moving from Tools to Deliverables and Outcomes” on 27–30 March 2018, in Nairobi, Kenya. Participants were from Bioversity International, International Center for Tropical Agriculture (CIAT), International Potato Center (CIP), International Institute of Tropical Agriculture (IITA), University of Florida (UF), and Wageningen University (WUR). The participants reflected on advancing the development and application of tools that are part of the RTB crop seed systems toolbox. Topics for discussion included the completeness of the toolbox, how to prioritize tools, and exploring possible synergy between the tools and ensuring their applications.